When Writing Gets Rough: Writing Assistance Towards the Transformation of Educational Landscape - Liriolyn Pacursa; Analyn D. Almoite (SALTeL Journal (Southeast Asia Language Teaching and Learning), 2022)
Writing is one of the skills that has been harmed throughout these tough times of pandemics since students have been unable to strengthen their writing skills. The purpose of this study was to see how well BTLEd students could write the various elements of an argumentative essay in the (Pre-Test) and (Post-Test) phases. The pre-test and post-test essay scores of the 65 BTLEd students were analyzed using a mixed-method technique. The students' degree of competence in writing the various elements of the argumentative essay in their pre-test was described as progressively competent, according to the findings. However, the students' post-test performance improved after they completed their virtual writing intervention. Furthermore, it was noted that there is a significant difference between the pre-test and post-test performance of the respondents. Students' competency in writing must be continuously monitored and evaluated in order to improve their skills in writing argumentative essays.